The Embryonic Chick Femur Organotypic Model as a Tool to Analyze the Angiotensin II Axis on Bone Tissue - Thais Francini Garbieri; Victor Martin; Carlos Ferreira Santos; Pedro de Sousa Gomes; Maria Helena Fernandes (MDPI AG, 2021)
Activation of renin-angiotensin system (RAS) plays a role in bone deterioration associated with bone metabolic disorders, via increased Angiotensin II (AngII) targeting Angiotensin II type 1 receptor/Angiotensin II type 2 receptor (AT1R/AT2R). Despite the wide data availability, the RAS role remains controversial. This study analyzes the feasibility of using the embryonic chick femur organotypic model to address AngII/AT1R/AT2R axis in bone, which is an application not yet considered. Embryonic day-11 femurs were cultured ex vivo for 11 days in three settings: basal conditions, exposure to AngII, and modulation of AngII effects by prior receptor blockade, i.e., AT1R, AT2R, and AT1R + AT2R. Tissue response was evaluated by combining µCT and histological analysis. Basal-cultured femurs expressed components of RAS, namely ACE, AT1R, AT2R, and MasR (qPCR analysis). Bone formation occurred in the diaphyseal region in all conditions. In basal-cultured femurs, AT1R blocking increased Bone Surface/Bone Volume (BS/BV), whereas Bone Volume/Tissue Volume (BV/TV) decreased with AT2R or AT1R + AT2R blockade. Exposure to AngII greatly decreased BV/TV compared to basal conditions. Receptor blockade prior to AngII addition prevented this effect, i.e., AT1R blockade induced BV/TV, whereas blocking AT2R caused lower BV/TV increase but greater BS/BV; AT1R + AT2R blockade also improved BV/TV. Concluding, the embryonic chick femur model was sensitive to three relevant RAS research setups, proving its usefulness to address AngII/AT1R/AT2R axis in bone both in basal and activated conditions.